User Satisfaction for an Augmented Reality Application to Support Productive Vocabulary Using Speech Recognition. (3rd June 2018) - Che Hashim, Nurhazarifah; Abd Majid, Nazatul Aini; Arshad, Haslina; Khalid Obeidy, Waqas
Abstract : The aim of this paper is to evaluate user satisfaction based on System Usability Scale (SUS) questionnaire on Augmented Reality (AR) application for productive vocabulary using speech recognition. There is still lack of research focus on user satisfaction towards the use of AR-based app using speech recognition for vocabulary learning in early education. The first objective of this paper is to develop an AR application for children using speech recognition to enhance productive vocabulary learning that integrates visual script (orthography) and audio (phonology). The second objective is to evaluate and identify the user satisfaction in enhancing productive vocabulary methods by combining AR technology and speech recognition to the parents and teachers by doing a mixed method testing such as questionnaire and interview. To achieve this, an interview session was conducted with the experts and SUS questionnaire was given to the teachers and parents of the student to evaluate user satisfaction. The results show that the research hypotheses of this study were successfully achieved. It revealed that the teachers and students were satisfied with the application based on SUS score (SUS score > 68). Since the total SUS score is 80.3, which is above average, it shows that they were satisfied with the overall application. Apart from that, the mean of the usability study based on questionnaire also shows that the users have found that this application is usable in terms of learnability study and that this application is easy to use.